The evolution of the green finance agenda - Institutional anchoring and a survey-based assessment for Austria - Daniela Kletzan-Slamanig; Angela Köppl (Austrian Institute of Economic Research (WIFO), 2021)
A comprehensive restructuring of economies and a massive increase of investments in climate-friendly technologies, infrastructures, and R&D is needed for reaching the Paris targets. The EU has launched a process for greening the financial sector emphasising the need for new instruments and financial market regulation for aligning investments to sustainability. This chapter summarises research on two topics: firstly, what are the main political strategies, especially at EU level, to support green finance, and secondly, which are the key supporting factors, barriers and actors for an upscaling of green investments? To assess the relevance of green finance in the financial market and climate policy (with focus on Austria) an expert survey was conducted. It delivers insights on promising policies and strategies for fostering the growth of green finance. Conclusions can be drawn on instruments (like carbon pricing) that should be integrated in post-COVID-19 stimulus packages to ensure a Paris-aligned recovery.
Keywords: Q54; Q58; G11; G18; 330; Green finance; EU sustainable finance strategy; survey data; low-carbon transition; green recovery